Inverse Relationship Between Serum Carotenoid Levels and Cardiovascular‐Kidney‐Metabolic Syndrome Among the General Adult Population - Mengli Chen; Shuyue Cai; Qinfeng Jia; Yifang Suo; Yuan Tang; Yanping Shi; Xu Zhu; Haifeng Zhang (Journal of Diabetes)
ABSTRACT Objective To examine the relationship between serum carotenoid levels and cardiovascular‐kidney‐metabolic (CKM) syndrome in a representative sample of US adults. Methods Data from the fasting subsample of the NHANES 2017–2018 were analyzed using a survey‐weighted approach to ensure the findings are representative of the broader US adult population. Serum levels of α‐carotene, β‐carotene, β‐cryptoxanthin, lutein/zeaxanthin, and lycopene were measured using high‐performance liquid chromatography. CKM syndrome stages were defined according to the 2023 American Heart Association guidelines, with advanced CKM syndrome categorized as stages 3 or 4. Associations between serum carotenoids and advanced CKM syndrome were assessed using logistic regression and weighted quantile sum (WQS) regression. Results The study included 1671 adults aged 20 years and older, with a mean age of 48.7 years and a gender distribution of 50.9% female and 49.1% male. Higher serum levels of α‐carotene, β‐carotene, α‐cryptoxanthin, lutein/zeaxanthin, and lycopene were inversely associated with advanced CKM syndrome. Specifically, compared to the lowest quartile, the highest quartile of α‐carotene had an odds ratio (OR) of 0.29 (95% CI: 0.16–0.55), β‐carotene 0.35 (95% CI: 0.16–0.78), α‐cryptoxanthin 0.23 (95% CI: 0.11–0.49), lutein/zeaxanthin 0.26 (95% CI: 0.14–0.48), and lycopene 0.58 (95% CI: 0.35–0.98). However, β‐cryptoxanthin did not show a significant association. Moreover, the combined effect of all carotenoids was significantly negatively correlated with advanced CKM syndrome (OR = 0.67, 95% CI: 0.53–0.86), with lutein/zeaxanthin contributing the most (44.56%). Conclusions Elevated serum carotenoid levels are inversely associated with the prevalence of advanced CKM syndrome in a dose‐dependent manner, with this association remaining consistent across diverse demographic and health subgroups.